Screening of oat cultivars developed in omsk for conditions of the southern foreststeppe in Western Siberia - Oksana Aleksandrovna Yusova; Petr Nikolayevich Nikolaev; Nikolay Ivanovich Aniskov; Irina Vladimirovna Safonova (RUDN Journal of Agronomy and Animal Industries, 2021)
Spring oats are one of the most important crops among grain crops, and they are well adapted to the conditions of Western Siberia. To realize qualitative and quantitative characteristics of yield and increase productivity, new varieties should be characterized by responsiveness to changing environmental factors (adaptability) with sufficient potential productivity and ability to realize it even in the stressful conditions of this region. The aim of the research was to determine adaptive properties of spring oat cultivars developed in Omsk Agrarian Scientific Center. The experiments were carried out on the experimental fields of the Omsk Agrarian Scientific Center, located in the southern forest-steppe zone of Western Siberia, in 2011-2019. The st following adaptability parameters were calculated: stress tolerance Kst (according to A.V. Bykov), homeostaticity Hom (V.V. Khangildin), breeding value of cultivar Sc (according to N.A. Orlyansky), genotypic effect Ɛi (B.P. Guriev), coefficient of variation V and coefficient of uniformity B (B.A. Dospekhov), resilience of stability index У (R.A. Udachin and P.A. Golovchenko), rate of reaction of varieties to the environmental conditions Re (V.V. Novokhatin), equivalent plasticity Wi (C. Wricke). Using a significant number of indicators to obtain a final assessment of adaptability, a ranking of cultivars was carried out. Among hulled oat cultivars, Orion (control), Irtysh 13 and Irtysh 21 had increased adaptability (the sum of the ranks was 23, 35 and 36, respectively). In naked oat cultivars, Progress was more stable (the sum of the ranks was 79). These cultivars are recommended for cultivation in conditions of the southern forest-steppe of Western Siberia.